Determinasi Kinerja Karyawan Berbasis Lingkungan Kerja, Kompensasi, dan Keterampilan Kerja: Kasus PT Indonesia Morowali Industrial Park - Siadi Siadi; Mansyur Ramly; Zaenal Arifin (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This associative study aims to analyze the influence of work environment, compensation, and work skills on employee performance at PT Indonesia Morowali Industrial Park. This study involved 100 employees of PT Indonesia Morowali Industrial Park who were selected using the Slovin formula. Data collection was carried out using an instrument in the form of a questionnaire, the answers of which were evaluated using a Likert scale. The data that had been obtained were then analyzed using a multiple linear regression approach to determine the relationship between the variables studied. The results of the study suggest that the work environment has a positive and significant effect on employee performance. Likewise, compensation has a positive and significant impact on employee performance. Furthermore, work skills have a positive and significant effect on improving employee performance. Following up on these findings, management is advised to strategically focus attention on the work environment, compensation, and skills development through a supportive work climate, fair compensation, and ongoing training to improve employee performance and company competitiveness.